Severe form of Legionnaires' disease in an immunocompetent patient - Andrijević Ilija; Matijašević Jovan; Považan Đorđe; Kojičić Marija; Batranović Uroš (Vojnosanitetski Pregled, 2009)
Background. Legionnaires' disease (LD) is a pneumonia caused by Legionella pneumophila (LP). The disease occurs more often in immunocompromised persons and can be manifested by severe pneumonia, multiple organ failure and has a high mortality. Case report. Immunocompetent patient, male, 53- year old, with severe form of LB had fever, cough, weakness and diarrhea as the initial symptoms of the disease. Laboratory results showed increased number of leukocytes, increased values of acute phase proteins, liver enzymes and hyponatremia. Computed tomography of the chest showed the marked inflammatory lesions on both sides. Pathohystological analysis of the samples retrieved by bronchoscopy pointed to a pneumonia, and diagnosis of LD was confirmed by positive urine test for LP antigen. Later, the disease was complicated by acute adult respiratory distress syndrome (ARDS). Treatment with antibiotics (erythromycin, rifampicin, azithromycin) combined with ARDS treatment led to a clinical recovery of the patient together with complete resolution of inflammatory lesions seen on chest radiography. Conclusion. In severe pneumonias it is necessary to consider LD in differential diagnosis, perform tests with aim of detecting LP and apply adequate antibiotic treatment in order to accomplish positive outcome of the therapy and prevent complications.